Implementation of the Policy on Fulfilling the Right to Inclusive Education for Persons with Intellectual Disabilities - Hilyawan, Yovie Irvandi; Sudarmo, Sudarmo; Sudibyo, Desiderius Priyo (Publik : (Jurnal Ilmu Administrasi), 2025)
This study aims to analyze the implementation of inclusive education policies for people with intellectual disabilities in Surakarta City. Although inclusive policies have been regulated nationally and regionally, their implementation at the school level still faces challenges in terms of communication, resource readiness, implementer disposition, and bureaucratic structure. This study employed a qualitative descriptive approach, utilizing data collection techniques that included in-depth interviews, observation, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. The results indicate that the dissemination of policy information is uneven, with the disability community playing a crucial role as an effective link for communication. Human resources and infrastructure still need to be strengthened, especially in teacher training and administrative access to budget support. Implementer attitudes show diversity, but direct experience accompanying students with disabilities has been shown to foster more substantial commitment. The bureaucratic structure still faces complex coordination and administrative barriers. This study contributes to the field by identifying the strategic role of the community in policy dissemination, non-technical administrative barriers to resource access, and the importance of micro-experiences in strengthening the commitment of inclusive policy implementers.